Pengaruh Snowball Throwing Terhadap Keterampilan Berpikir Kritis Siswa Pada Pelajaran Fikih - Syifa Nurjanah; Khalid Ramdhani; Sya’roni Ma’shum (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study examines the effect of the Snowball Throwing method on the critical thinking skills of eighth-grade students in the Fikih subject at MTsN 2 Karawang. The background of the study lies in the low levels of student participation and critical thinking in Fikih learning, which is often teacher-centered and theoretical. This research positions the Snowball Throwing model as a cooperative strategy that encourages students to ask questions, express opinions, and understand information actively. The study employed a quantitative approach using a quasi- experimental design with a pretest-posttest control group. The sample consisted of two classes divided into experimental and control groups. Data analysis included tests of normality, homogeneity, and a t-test. The results revealed a significant difference between the pretest and posttest scores of the experimental group compared to the control group. These findings demonstrate that the Snowball Throwing method significantly enhances students' critical thinking skills. A key contribution of this study is its emphasis on the effectiveness of interactive learning in fostering higher-order thinking skills within Islamic education, particularly in the subject of Fikih.